Paul's Eschatological Anthropology: The Esō Anthrōpos and The Intermediate State. (January 2017) - Harding, Sarah
Advances in the study of Paul's anthropology during the past century have been limited, particularly because of dominant theological approaches that leave many unresolved issues regarding the apostle's understanding of humans. This article introduces a new approach, which grounds Paul's anthropological discourse in eschatology, and underscores the importance of transformation. Through the application of this new approach, the esō anthrōpos, instantiated in believers through the Holy Spirit, is shown to be the locus of renewal, and to encompass the entire human. A clear understanding of this concept provides support for the postulation of an intermediate state in Paul's symbolic universe, a claim that is contested by many scholars.